Gestión de procesos administrativos en la Piladora Genesis del Cantón Jujan - Mantuano Herrera, Oswaldo Joel (2020)
The purpose of this case study was to analyze the different causes of mismanagement of administrative processes at La Piladora Génesis. Over time the company has undergone significant changes in which various problems have arisen, which lead to the management of inadequate administrative processes in the company, such as: lack of investment in the infrastructure of the premises where it operates, lack of updated technological equipment , low product quality due to the use of machinery in poor condition, low productivity, little competitiveness in the market, among other inconveniences that affect the income of said business.